ALKALINE MEDIUM MN(VII) OXIDATION OF D-SORBITOL AND D-DULCITOL: INSIGHTS INTO SUBSTRATE INHIBITION MECHANISMS - Akinwumi, Oluwafemi Adebayo; Olatunj, Adeola Adesola; Adekunle, Olamide Ayodele (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Sugar alcohols, also known as polyols, serve as valuable sugar substitutes due to their similar sensory properties to sugars, but with reduced calorie content and fewer negative health effects. Unlike traditional sugars, sugar alcohols are not completely absorbed into the bloodstream, making them a healthier alternative for managing blood sugar levels and protecting against tooth decay. This study focuses on the oxidation kinetics and mechanisms of two specific sugar alcohols, D-sorbitol and D-dulcitol, by alkaline KMnO4, shedding light on their reactivity and potential applications.